2017
DOI: 10.1155/2017/6098107
|View full text |Cite
|
Sign up to set email alerts
|

The eIF4E2‐Directed Hypoxic Cap‐Dependent Translation Machinery Reveals Novel Therapeutic Potential for Cancer Treatment

Abstract: Hypoxia is an aspect of the tumor microenvironment that is linked to radiation and chemotherapy resistance, metastasis, and poor prognosis. The ability of hypoxic tumor cells to achieve these cancer hallmarks is, in part, due to changes in their gene expression profiles. Cancer cells have a high demand for protein synthesis, and translational control is subsequently deregulated. Various mechanisms of translation initiation are active to improve the translation efficiency of select transcripts to drive cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 106 publications
(170 reference statements)
0
24
3
Order By: Relevance
“…3F). Mechanisms by which HIF-2␣ acted at the 3= UTRs of the rHREs of select mRNAs along with RBM4 to mediate joining of the 5= end and eIF4E2 were initially proposed (16,22,47). It is important to note that cap-binding assays are performed with m 7 GTP bound to agarose beads and not to an mRNA (48).…”
Section: Discussionmentioning
confidence: 99%
“…3F). Mechanisms by which HIF-2␣ acted at the 3= UTRs of the rHREs of select mRNAs along with RBM4 to mediate joining of the 5= end and eIF4E2 were initially proposed (16,22,47). It is important to note that cap-binding assays are performed with m 7 GTP bound to agarose beads and not to an mRNA (48).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the role of cap-dependent protein translation in oncogenesis, and translation initiation factors have long been recognized as potential sources of dysregulation during the oncogenic process. [19][20][21] However, the role of nuclear cap-binding protein 1 in the development and progression of cancer is not well F I G U R E 6 NCBP1 together with NCBP3 regulates CUL4B mRNA expression. A, RNA immunoprecipitation assay.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other studies suggest chronically hypoxic cancer cells are able to take advantage of a non-canonical cap-dependent pathway, which is both HIF-2α dependent and distinct from mTORC1 suppression, thus maintaining de-novo protein synthesis and tumour growth under chronic hypoxia. 55,56 There are currently no direct links to PCa 57 and general therapeutic approaches are at an early stage, 56 but progress in this field should be followed closely.…”
Section: The Biochemistry Of Hypoxia: Implications For Prostate Cancermentioning
confidence: 99%